PERKEMBANGAN INDUSTRI PISANG SALE DI KECAMATAN BATHIN III DAN KECAMATAN BUNGO DANI KABUPATEN BUNGO - sari, rika reskika; Syahar, Fitriana (DEPARTEMEN GEOGRAFI FIS UNP, 2024)
This study aims to determine 1). analysis of supporting factors for the banana sale industry in Bhatin III and Bungo dani sub-districts Bungo district (2) Mapping of changes in the growth of the banana sale industry from 2010-2020 in Bhatin III and Bungo dani sub-districts Bungo district (3) Analyzing the development of the banana sale industry in Bhatin III District and Bungo Dani District and Bungo District. The research method used in this study is a survey method with quantitative analysis. The type of data used in this study consisted of primary data and secondary data. Primary data sources are obtained from interviews and questionnaires with informants who have the development of the banana sale industry, and secondary data sources from archives, and documents on population data and population density sourced from the Central Statistics Agency, road network maps, administration map displays and building data from the Department of Public Works/Bappeda Bungo Regency